KETERKAITAN SELF EFFICACY DAN LOCUS OF CONTROL DENGAN PENINGKATAN KINERJA KARYAWAN PADA PT. MANDALA MULTI FINANCE, TBK. SUMBAWA BESAR - Rachman, Rosyidah; Sutama, I Nyoman; Halima, H (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to know the relationship between self-efficacy and locus of control with employee performance improvement at PT. Mandala Multi Finance, Tbk. Sumbawa Besar. The type of this study was associative that aims to examine the effect of self-efficacy (X1) and locus of control (X2) on employee performance at PT. Mandala Multi Finance, Tbk. Sumbawa Besar (Y). The type of data used was quantitative data obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 53 employees of PT. Mandala Multi Finance, Tbk. Sumbawa Besar. The data analysis tool used was multiple linear regression, partial hypothesis test (t test), simultaneous hypothesis test (F test), and coefficient of determination test (R2). The results of the study showed that self-efficacy (X1) and locus of control (X2) had a positive and significant effect on employee performance at PT. Mandala Multi Finance, Tbk. Sumbawa Besar (Y), either partially or simultaneously. The percentage contribution of self-efficacy (X1) and locus of control (X2) in effecting employee performance at PT. Mandala Multi Finance, Tbk. Sumbawa Besar (Y) was 94.7%, while the remaining of 5.3% was effected by other variables not examined in this study, such as leadership style, work motivation and compensation.